Line Balancing Analysis of a Multi-Products Processing with a Single Type of Supply - Mohd Syahidan, Kamarudin; Mohd Zaidi, Sidek (Knowledge Transfer Centre, USM, 2015)
To compete in an ever growing manufacturing environment, companies have to improve their productivity. This study describes the improvement activities of an SME company in Kuantan, Pahang by using a line balancing technique. With these improvement techniques, the company managed to reduce the total time required to 70% and increased the production to 5%. This study also proposes processing line improvements, using simulation methods, by focusing on re-layout the workstations from an unsystematic arrangement of workstation to a single production line for each type of product and managing the workload distribution on the operators. Using a process simulation approach, this paper compares the performance of the production model using unsystematic arrangement production line with the single systematic arrangement of production lines. The feasibility of this solution is then discussed.